Transparent Electronics Based on Transfer Printed Aligned Carbon Nanotubes on Rigid and Flexible Substrates - Ishikawa, Fumiaki N; Chang, Hsiao-kang; Ryu, Koungmin; Chen, Po-chiang; Badmaev, Alexander; Gomez De Arco, Lewis; Shen, Guozhen; Zhou, Chongwu (ACS nano, 2009)
We report high-performance fully transparent thin-film transistors (TTFTs) on both rigid and flexible substrates with transfer printed aligned nanotubes as the active channel and indium−tin oxide as the source, drain, and gate electrodes. Such transistors have been fabricated through low-temperature processing, which allowed device fabrication even on flexible substrates. Transparent transistors with high effective mobilities (∼1300 cm2 V−1 s−1) were first demonstrated on glass substrates via engineering of the source and drain contacts, and high on/off ratio (3 × 104) was achieved using electrical breakdown. In addition, flexible TTFTs with good transparency were also fabricated and successfully operated under bending up to 120°. All of the devices showed good transparency (∼80% on average). The transparent transistors were further utilized to construct a fully transparent and flexible logic inverter on a plastic substrate and also used to control commercial GaN light-emitting diodes (LEDs) with light intensity modulation of 103. Our results suggest that aligned nanotubes have great potential to work as building blocks for future transparent electronics.